ä½¿ç”¨ç›´è§‚æ³•æé«˜KEMALA BHAYANGKARIåˆä¸äºŒå¹´çº§å¦ç”Ÿ åŠ¨è¯çš„æŽŒæ¡èƒ½åŠ› - Indah, Mutiara Permata; Thamrin, Lily; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIntuitive method is method that uses vision directly in prosea teaching. Intuitive methods provide many convieniences in the teaching process. In a pleasant classroom atmosphere,students will more quickly understand the contents of teaching. The author uses intuitive methods in conducting research,because in teaching intuitive methotds there are 4 ways of teaching,namely using the classroom,using pictures,using tools date are accompanied bye images,and using movement,the goal is to understand whether using intuitive methods can the ablity students in mastering verbs in Chinese.To prove the effect of intuitive methods in mastering Chinese verbs,writing conducts research Â in grade 2 of kembala bhayangkari middle school. After the research, the results obtained by writing are clearly using the coreativie method to improve the student ability in mastering Chinese verbs, while also increasing student test scores. Student final test scores are higher than the initial test scores. The average value of a studentâ€™s final test increases to 80,45% of authors use the KKM score as a graduation standard of 70. Based on the school KKM score after using the intuitive methods,the percentage of students who pass the final test is 90% this indicates that the intuitive method has an effect so that the remainder can understand the contents of the teaching and can also master the verbs of Chinese.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords: Intuitive methods , Verb , Master in verb